Stability of the Evolutionary Game System and Control Strategies of Behavior Instability in Coal Mine Safety Management - Xinhua Wang; Rongwu Lu; Hao Yu; Dan Li (Complexity)
In this paper, we try to find the right control method for the game behavior instability in coal mine safety management. Through the analysis and comparison of the system stability with inflexible and flexible costs and penalties, it can be concluded that the dynamical game system with flexible costs (incentive rewards) and flexible penalty mechanism can significantly reduce the dynamics of unsafe behaviors in coal mine safety supervision. A combined mechanism of incentive rewards and flexible penalty is put forward to improve the stability of the dynamical system and control the instability of behaviors effectively. The results of model simulation show that the combined mechanism has very good property and can optimize and control the instability of behaviors and strategies of the interested parties. Based on the theoretical conclusions, some control strategies and policy advice are proposed for the improvement of the system and measures of safety management for government departments.